Vegetation cover fraction and the residential distribution of child-rearing households in urban Tokyo and Osaka: An ecological cross-sectional analysis - Moe Otani; Daisuke Matsushita (PLoS ONE, 2026)
In Japan, promoting the long-term settlement of child-rearing households is critical to counteract community decline driven by a falling birthrate and an aging population. Most previous studies on residential location preferences among child-rearing households have relied on self-reported data, and a lack of quantitative evidence based on geospatial and demographic indicators still remains. This ecological cross-sectional study examined the association between vegetation cover fraction (VCF) and the residential distribution of child-rearing households by analyzing the relationship between VCF and the proportion of children (POC) in Tokyo and Osaka. Correlations between VCF and the POC were calculated for all town blocks with VCF values below 0.5 (representing urban and suburban areas rather than forested or rural regions), stratified by distance from the city center and school-age groups, and adjusted for neighborhood environmental and transportation accessibility factors. VCF showed a positive association with the POC even after adjustment (Tokyo: 4,814 town blocks, coefficient: 0.05; Osaka: 7,337 town blocks, coefficient: 0.040). Significant positive associations were observed within 0–15 km from the city center in Tokyo and within 5–15 km in Osaka, but not beyond 15 km. The strongest associations in Tokyo were observed within 5 km for preschool-aged children and 5–10 km for older students, while those in Osaka were noted within 5–10 km for younger children and 20–25 km for junior high school students. These findings suggest that the residential distribution of child-rearing households in urban areas is positively associated with nearby urban greenery.